Common Fixed Point Theorems in Extended Rectangular b-Metric Spaces - Rakesh Tiwari; Rajesh Patel, Rajesh Patel (International Journal of Applied Mathematical Research, 2024)
In this paper, we establish common fixed point theorems for quadruple weakly compatible mappings satisfying a new generalized contraction condition. Our results generalize the corresponding result of Budi Nurwahyu et al. [6]. Non-trivial examples are further provided to support the hypotheses of our results.